2002
DOI: 10.1021/es011051e
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation of Persistent Organochlorine Accumulation in Birds from Lake Baikal, Russia, and the Role of the South Asian Region as a Source of Pollution for Wintering Migrants

Abstract: Concentrations of persistent organochlorines (OCs) such as polychlorinated biphenyls (PCBs), DDT and its metabolites (DDTs), hexachlorocyclohexane isomers (HCHs), and chlordane compounds (CHLs) were determined in whole body soft tissue homogenates and in muscles of resident and migratory birds collected from Lake Baikal, Russia. The residue pattern in both resident and migratory birds was in the following order: PCBs > DDTs > HCHs > CHLs. OC concentrations in migratory birds varied, depending on the feeding ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 43 publications
4
21
0
Order By: Relevance
“…Among mono-ortho-PCB congeners (PCB 105,118,123,156,157 and 169), PCB 105 was the major contributor to TEQ concentrations (53.8%), followed by PCB 156 and PCB 118. This pattern was similar to other studies on predatory birds from northern China (Chen et al, 2009b) and aquatic birds from Russia and Switzerland (Zimmermann et al, 1997;Kunisue et al, 2002). The levels of TEQ in light-vented bulbul ranged from 0.25 to 912 pg/g lw.…”
Section: Risk Assessmentsupporting
confidence: 90%
“…Among mono-ortho-PCB congeners (PCB 105,118,123,156,157 and 169), PCB 105 was the major contributor to TEQ concentrations (53.8%), followed by PCB 156 and PCB 118. This pattern was similar to other studies on predatory birds from northern China (Chen et al, 2009b) and aquatic birds from Russia and Switzerland (Zimmermann et al, 1997;Kunisue et al, 2002). The levels of TEQ in light-vented bulbul ranged from 0.25 to 912 pg/g lw.…”
Section: Risk Assessmentsupporting
confidence: 90%
“…In addition, they are long-distance migrants that visit many countries with poor pollution control practices, increasing their risk of contaminant exposure (Kunisue et al 2002). Areas of Central and South America are of particular concern because mercury contamination is significantly increasing due to artisanal small-scale gold mining (UNEP 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, release from electrical equipment, leakages of hydraulic fluids from shipping vessels and old transformers and capacitors could be potential reason for elevated PCBs contamination encountered in mussels from coastal waters of these countries (Ramu et al 2007). Using resident and migratory birds as bioindicators, high concentrations of organochlorine insecticides and PCBs were found in birds collected at stopover/wintering areas of tropical Asian developing countries and Russia/Japan, respectively (Kunisue et al 2002aMinh et al 2002). To substantiate our findings with further evidence on pollution sources of organochlorines, we collected human breast milk from Asian countries and determined residue levels of contaminants ( Table 1).…”
Section: Status Of Contamination and Distributionmentioning
confidence: 67%
“…In case of dioxins, it is reported that 1-3 monthold infants absorb above 90% of most dioxin congeners present in their mothers milk (Dahl et al 1995;McLachlan 1993), hence they may be exposed to relatively high levels of POPs during this period. To understand the magnitude of exposure to POPs by infants, we estimated daily intake (DI) from the levels of these contaminants in human breast milk observed in Asian countries, based on the assumption that an infant ingests 700 ml milk per day and the weight of an infant is 5 kg (Kunisue et al 2002a(Kunisue et al , b, 2004aMinh et al 2004;Sudaryanto et al 2005aSudaryanto et al , b, 2006 and compared the values with the guideline standards proposed by WHO and Health Canada (Van Leeuwen et al 2000;Oostdam et al 1999).…”
Section: Risk Assessment For Infantmentioning
confidence: 99%